2017
DOI: 10.1021/acs.nanolett.7b04904
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterns of Surface-Bound EphrinB1 Produce Multivalent Ligand–Receptor Interactions That Tune EphB2 Receptor Clustering

Abstract: Here we present a nanostructured surface able to produce multivalent interactions between surface-bound ephrinB1 ligands and membrane EphB2 receptors. We created ephrinB1 nanopatterns of regular size (<30 nm in diameter) by using self-assembled diblock copolymers. Next, we used a statistically enhanced version of the Number and Brightness technique, which can discriminate-with molecular sensitivity-the oligomeric states of diffusive species to quantitatively track the EphB2 receptor oligomerization process in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…Many interdisciplinary efforts have been made to control nanoscale molecular interactions at cellular boundaries.F or example,several technologies that enable the local control of the spatial distribution of cell surface receptors have been developed, such as molecular nanopatterns,m agnetic actuation, biopolymers,a nd DNAn anostructures. [18][19][20][21][22][23] Thef eatures of some important technologies to control the clustering of cell surface receptors are summarized in Table 1.…”
Section: Strategies For Controlling Cell-surface Receptor Clusteringmentioning
confidence: 99%
See 3 more Smart Citations
“…Many interdisciplinary efforts have been made to control nanoscale molecular interactions at cellular boundaries.F or example,several technologies that enable the local control of the spatial distribution of cell surface receptors have been developed, such as molecular nanopatterns,m agnetic actuation, biopolymers,a nd DNAn anostructures. [18][19][20][21][22][23] Thef eatures of some important technologies to control the clustering of cell surface receptors are summarized in Table 1.…”
Section: Strategies For Controlling Cell-surface Receptor Clusteringmentioning
confidence: 99%
“…[35] In ar ecent work, the Martinez group developed an ovel technique,t ermed enhanced Number and Brightness (eN&B), to measure the kinetics of eph-receptor oligomerization in live cells. [18] Thee N&B technique can discriminate between the oligomeric states of eph-B2 receptors with molecular sensitivity and quantitatively track the eph-B2 receptor oligomerization process in real time.T heir results indicated that randomly distributed surface-bound ligands were not sufficient to fully induce receptor aggregation. However,the nanopatterned ligands could effectively induce strong receptor oligomerization [18] (Figure 2).…”
Section: Molecular Nanopatternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multivalent interactions are ubiquitous in biology,w hich involve the bindingo fm ultiple ligandso fab iological entity to multiple binding pocketso rr eceptors of at arget, for example, ap rotein,v irus, bacterium, or cell. [1][2][3][4] Multivalent interactions have an umber of benefits over monovalenti nteractions, such as i) possessing higherb inding affinity;i i) standing ab etter chance of providing higher selectivity in target recognition;i ii) having stronger binding properties from weak homo-o rh eterogeneous ligands. [5] Scientists take these benefits to design new therapeutic entities,e specially those concerned with the allostericm odulation of the receptor [6] and the repetitive epitopes of antibodies.…”
mentioning
confidence: 99%